Conocimiento, poder y transformación digital en América Latina - Birle, Peter (2024)
The management of resources associated with knowledge is one of the most controversial and discussed topics of our time. Global debates and conflicts about the use, transfer, monopolization, democratization and diversification of knowledge are always linked to issues of social, political and economic power. New technologies and new media formats allow, on the one hand, better access to knowledge as a resource and, therefore, a greater degree of political and social participation by broader sectors of the population. At the same time, the valorization of knowledge by global corporations, for example through the sometimes illegal acquisition of data or the claim and enforcement of intellectual property rights, promotes the formation of knowledge monopolies that They serve commercial purposes and exacerbate social inequalities. Furthermore, the cultural and linguistic diversity of Latin America forces a fundamental questioning of Eurocentric epistemologies and a general reflection on the cultural dimensions of the production, transformation and storage of knowledge and on digital transformation. The contributions to this volume address the processes of production, transformation and storage of knowledge in Latin America from different disciplinary and national perspectives. Its multiple articulations and the dynamics of knowledge production in colonial and postcolonial contexts are taken into account. The volume represents an important contribution to global debates on the interaction between knowledge, power and digital transformation...